Electrodeposition study of the Cu-Zn-Mo system in citrate/sulfate medium - Santos, Hugo Sousa; Correa, Alessandra Alves; Gromboni, Murilo Fernando; Mascaro, Lucia Helena (Eclética Química, 2019)
Alloys and composites that contain molybdenum have been studied due to their excellent properties, such as corrosion resistance and catalytic activity. In this work, the parameters for Cu-Zn-Mo system electrodeposition were studied, such as deposition potentials and concentration of electroactive species. The deposition potentials were examined using cyclic voltammetry and anodic linear stripping voltammetry (ALSV), the deposit morphology was evaluated using scanning electron microscopy (SEM) and crystallographic characterization was carried out for X-ray diffraction (XRD). The voltammetry studies indicated co-deposition of the metals in potentials more negative than -1.2 V, and a potential deposition at -1.5 V was chosen. The coatings presented morphology compact with small agglomerated particles with cauliflower structures, and the content of molybdenum, copper, and zinc ranged from 5 to 8%, 30 to 40% and 20 to 28%, respectively.